Ice-sheet erosion and the stripping of Tertiary regolith from Baffin Island, eastern Canadian Arctic - Refsnider, K.; Miller, Gifford (Elsevier, 2013)
The erosion of glaciated regions and concomitant changes in ice sheet dynamics through the Pleistocene are poorly documented. The Baffin Island landscape, which has been shaped by the Foxe Sector of the Laurentide Ice Sheet (LIS), contains a variety of glacial and proximal glaciomarine sedimentary archives spanning the Pleistocene. We examine these records to better understand when Tertiary regolith was stripped from beneath the Foxe Sector of the LIS. Till on the interior plateaux of the island in areas with scoured bedrock have low chemical index of alteration (CIA) values, low meteoric 10Be (10Bemet) concentrations, and clay mineralogy consistent with erosion from an unweathered bedrock source. However, in some areas in between fiord onset zones, more weathered till is present, containing considerably higher CIA values, high 10Bemet concentrations, and secondary clay mineral weathering products, implying that the till has persisted on the landscape and weathered during successive glaciations. Using these weathering signatures, we analyze the coastal glaciogenic deposits of the Clyde Foreland Formation (CFF) at two sites for evidence of Tertiary regolith removal from the interior of Baffin Island by LIS erosion. Provenance indicators within the CFF demonstrate that Pleistocene LIS ice flow lines across Baffin Island have remained generally constant. The oldest CFF glaciogenic unit, likely representing one of the first, if not the first, LIS advances across Baffin Island, had high 10Bemet concentrations at the time of deposition consistent with extensive regolith erosion. Evidence of notably weathered sediment is absent in all younger units, suggesting that Tertiary regolith was likely largely stripped from the interior of the island by 1.6 0.2 Ma.